The Relationship between screen time and expressive language (active vocabulary and narrative production skills) in preschoolers - E.S. Oshchepkova; A.N. Shatskaya; Y.E. Makarevskaya; A.A. Tvardovskaya (Психологическая наука и образование)
Context and relevance. The study of the impact of electronic devices, particularly screen time (ST), on children's cognitive, emotional, and language development has become increasingly relevant in recent years, especially after the transition to fully or partially electronic forms of education. The influence of ST on language development is only beginning to be explored and shows contradictory results. Objective. To identify the relationship between a child's ST and the characteristics of their language development. Hypothesis. The negative impact of ST on language development would only be observed when ST exceeds the duration recommended by the WHO. Methods and Materials. The study involved 652 preschoolers (M = 70,4 months, SD = 4,53; 51% boys). Participants attended kindergartens in Moscow (74%), Kazan (13.5%), and Sochi (12,5%). Children were asked to "play with words" (i.e., complete a verbal and semantic fluency test) and then view a series of pictures and tell a story based on them. Parents completed a questionnaire indicating their child's ST duration on weekdays and weekends. Results. It was shown that ST duration is not significantly associated with the size of children's vocabulary but is associated with their ability to construct coherent narratives. Conclusions. The negative impact of ST is indeed observed only when it is excessive and, according to our study, affects more complex forms of speech (narratives). In the future, we consider it necessary to determine at what age these differences begin to manifest, as it can be assumed that by 70 months, lexical and grammatical skills are generally formed, and the negative impact primarily affects parameters that are actively developing at this age, namely, the construction of coherent narratives, their coherence, integrity, and structure.